Investigation of the Relationship between Chronic Endometritis Manifestations under Hysteroscope and CD138 Expression - Shuang Wang; FengHua Li; Wei Zhang; XiaoLong Sui; CuiFang Hao (Applied Bionics and Biomechanics)
Background and Objective. Chronic endometritis (CE) displays different manifestations under hysteroscope and yields different CD138 immunohistochemistry (IHC) outcomes. This study was designed to probe links across different CE manifestations under hysteroscopy and the IHC outcome of CD138, as well as the efficacy of antibiotic treatment. Methods. This study was performed to retrospectively analyze clinical cases of 523 CE patients from January 2018 to June 2020 that were confirmed by hysteroscopy before in vitro fertilization. Based on manifestations of CE under hysteroscopy, the cases were divided into three cohorts, i.e., hyperemia cohort where the patients had diffuse endometrium hyperemia; endometrial micropolyp cohort, and endometrial stroma edema and hyperplasia cohort. Small amount of endometrial tissue was collected from the patients, and CD138 IHC examination was performed. According to the results of CD138 IHC, positive patients were given antibiotic treatment (doxycycline 100 mg BID orally for 14 days), and hysteroscopy was performed again after treatment to check the efficacy of antibiotics. Results. In the comparison of overall status for all patient cohorts, infertility type, BMI, bFSH, bLH, bP, bT, PRL, AMH, and CA125 were varied markedly across all cohorts (P<0.05), with predominant incidences of polycystic ovary syndrome (PCOS) peaking within hyperemia cohort. Incidence/diagnostic rate for CD138 within hyperemia cohort was 10.06%, which was lower than the 63.16% in micropolyp cohort and 74% in edema and hyperplasia cohort (P<0.05). No major variation existed within CD138 across micropolyp cohort/edema and hyperplasia cohort (P>0.05). After CD138-positive CE patients were treated with antibiotics, the effective rate (0/16) within hyperemia cohort was lower than micropolyp cohort (73.61%, 53/72) and edema and hyperplasia cohort (83.24%, 154/185) (P<0.05). The effective rate across micropolyp cohort/edema and hyperplasia cohort was not significantly different (P>0.05). Conclusion. Cases of diffuse endometrial hyperemia under hysteroscope had the lowest positive rate of CD138, and the effect of antibiotic treatment on these patients was poor. The positive rate of CD138 in patients with endometrial micropolyps and endometrial stroma edema and hyperplasia under hysteroscope was high, and the effect of antibiotic treatment was better.